Learning Styles and Academic Self-Efficacy: Active Student Engagement - Borousan, Negin; Canpolat, Ayşe Meliha (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
The aim of this study is to examine the relationships between academic self-efficacy, student engagement, and learning styles of students in different sports sciences departments, and to identify which learning style leads to more effective learning during student engagement. A total of 629 students, including 355 male and 274 female participants, voluntarily took part in the study. These students were enrolled in three universities in the Aegean region of Turkey: Ege University, Celal Bayar University, and Adnan Menderes University. Scales measuring academic self-efficacy, student engagement, and learning styles were used to assess the students' characteristics. Descriptive statistics, correlation analysis, cluster analysis, multivariate analysis of variance, and post-hoc tests were conducted for data evaluation. The results revealed a low positive correlation between the subdimensions of all three scales. Students with high academic self-efficacy preferred both verbal and visual learning styles, with a stronger preference for verbal styles. Additionally, male students with high academic self-efficacy used both verbal and visual learning styles more frequently than their female counterparts. These findings highlight the influence of self-efficacy on learning preferences and engagement in the academic context.